Kangaroo Mother Care Reduces Noninvasive Ventilation and Total Oxygen Support Duration in Extremely Low Birth Weight Infants - Xie, Xiaohua; Chen, Xueyu; Sun, Panpan; Cao, Aifen; Zhuang, Yanzhu; Xiong, Xiaoyun; Yang, Chuanzhong (American Journal of Perinatology, 2019)
Objective Evidence on the safety and influence of kangaroo mother care (KMC) in extremely low birth weight infants (ELBWIs) on ventilation is lacking.Study Design This is a retrospective cohort study performed in 145 ELBWIs on noninvasive mechanical ventilation from a tertiary center.Results The duration of nasal intermittent positive pressure ventilation (nIPPV) and continuous positive airway pressure (CPAP) ventilation was significantly shorter in infants with KMC compared with infants without (21 vs. 13.5 days, p = 0.001 and 29.5 days vs. 20.5 days, p = 0.001, respectively). The frequency of apnea during hospital stay was fewer in KMC infants, compared with no KMC (23 vs. 20 times, p = 0.002). Multiple linear regression analysis showed that KMC was an independent protective factor for shortening nIPPV/CPAP duration (β = −9.90, 95% confidence interval [CI] [−13.20, −6.60], p < 0.001), total supplemental oxygen support (β = −10.52, 95% CI [−16.73, −4.30], p = 0.001), and reducing times of apneas (β = −5.88, 95% CI [−8.56, −3.21], p < 0.001).Conclusion KMC benefits ELBWIs by shortening nIPPV/CPAP ventilation duration and total supplemental oxygen support, and reducing the frequency of apneas.
Keywords: kangaroo mother care; ventilation; apnea; preterm; extremely low birth weight